Presentation of the athlete's personal brand and delivering value to the sponsor - Wojciech Idzikowski (Nicolaus Copernicus University in Toruń, 2016)
The article is one of the author's first research steps on his way to identify the concept of personal brand communication of a sportsperson with the use of ICT tools. The cognitive stage of the article presents the overview of selected theoretical achievement, which may serve as the basis for further research considerations within this area. In the second part - designing - the author attempts to present the reference methodology thanks to which a sportsperson will be capable of presenting in a more economically effective way their personal brand and providing a higher level of value while cooperating with a sponsor.